Los programas de matemática para la enseñanza media costarricense (ING) - Barrantes, Hugo (2003)
We give a general historical summary of Costa Rican High School mathematics programs, dividing them into three stages: before 1964, from 1964 to 1991 and, finally, from 1991 to the present day. The current program (promulgated in 2001) is analyzed more carefully.